Genetic variation of Shad fish (clupeidae) inferred from cytochrome b gene - Nor Hafiza, Binti Abdullah (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The study reported on morphological variation of different species of genus Tenualosa from family of Clupeidae that has been purchased from Satok Market (Tenllalosa toIi, Tenllalosa macrllra, and TenualosQ i1isha). Each species are diagnosed initially by morphological character and the keys to species identification have been based, where possible, on the most obvious external characters. However, due to some reason such as misidentification due to damaged, poor specimen condition and ambiguous morphological features, we proceed to molecular technique inferred from cytochrome b gene. Both morphological variation and genetic variation was reported. The finding on genetic variation computed average percentage of the A (24.0%), T (27.9%), C (30.5%), and G (17.7%). The range of genetic distance between T macrura and T i1isha is between 13.9% - 20.7%. T macrura and T toli showed genetic distance between 13.5% - 20.8%. Whereas, for T i1isha and T toli, the differences is between 15.3% - 15.6% . Also, revealed the relationship with supported resolved bootstrap value (>50%) respectively distinct to their outgroup (Sardinella maderensis).